Tantangan Pengelolaan Penduduk di Kota Surabaya - Indahri, Yulia (Jurnal Aspirasi, 2017)
One issue that Indonesia facing today is the fast growing number of its population and it is concentrated in urban areas. BPS’ 2013 projection on rural-urban migration shows that in 2025, rural-urban migration, or commonly refer to as urbanisation, will increace to 60 percent, from 56,7 percent in 2020. This study seeks to determine the trend of growing number of population migration in the City of Surabaya, and social problems that might occur due to migration to the City. From the discussion it is understood that some regulations related to migration being excersided in the City would have served as a positive contibution in dealing with ruralurban migration in the future. From data gathered from the Office of the Government of the City in 2016, it can be concluded that problems, especially social problems, occor as the results of urbanisation in Surabaya are manageble due to established and strick policy from top leaders of Surabaya City. Other problem is the lack of information dissemination, although the Government of the City continues to settle the problem.Salah satu permasalahan penting yang dihadapi Indonesia saat ini adalah pesatnya pertumbuhan dan konsentarasi penduduk di perkotaan. Proyeksi BPS di tahun 2013 terhadap migrasi desa kota memperlihatkan bahwa di tahun 2025, migrasi desa kota, atau yang lebih sering disebut dengan urbanisasi, akan naik menjadi 60 persen dari sebelumnya 56,7 persen di tahun 2020. Kajian ini ingin menjawab pertanyaan mengenai perkembangan migrasi penduduk di Kota Surabaya dan apa saja permasalahan sosial yang muncul akibat migrasi penduduk di Kota Surabaya. Dari pembahasan akan terlihat kebijakan migrasi seperti apa yang telah diterapkan di Kota Surabaya dan dirasakan dapat membantu penanganan masalah migrasi desa kota di masa yang akan datang. Dari data yang diperoleh dari Pemerintah Kota Surabaya di tahun 2016, dapat disimpulkan bahwa permasalahan urbanisasi di Kota Surabaya, terutama permasalahan sosial, dapat ditanggulangi karena ada ketegasan kebijakan dari pimpinan tertinggi di Kota Surabaya. Permasalahan yang masih ditemui adalah kurangnya sosialisasi, walaupun Pemerintah Kota terus berupaya menyelesaikan masalah tersebut.